IMPLEMENTATION OF SAP NO.12 CONCERNING OPERATIONAL REPORTS OF TANJUNG BALAI CITY - Yose Sinambela, Hendry Glenn; Michael Panggabean, Gilbert Partogi; Muda, Iskandar (JIAR : Journal Of International Accounting Research, 2025)
Public financial management reform in Indonesia has advanced since the implementation of accrual-based accounting under Government Regulation No. 71 of 2010. One key outcome is the inclusion of the Operational Report (Laporan Operasional/LO), which provides a comprehensive overview of financial performance. In Tanjungbalai City, the LO plays an important role in promoting transparency and accountability amid limited fiscal capacity. This study analyzes the Operational Report of the Tanjungbalai City Gov ernment for the 2023/2024 fiscal year using a descriptive quantitative method based on secondary data. The analysis compares financial figures, evaluates effectiveness and efficiency ratios, and identifies fiscal trends. Results show that total revenue in 2024 decreased by 3.78% due to a 32.32% drop in locally generated revenue, while tran sfer revenue rose by 2.25% and expenditures fell by 8.97%. The oper ational deficit declined sharply from Rp 42.8 billion in 2023 to Rp 4.6 billion in 2024an 89.25% improvementindicating better fiscal balance and efficiency. Thus, the LO serves as a vital tool for evaluating government accountability and financial performance